P-185 Clinical, Endoscopical and Histological Correlation in Ulcerative Colitis Patients. (February 2017) - Fluxa, Daniela; Flores, Lilian; Ibáñez, Patricio; Lubascher, Jaime; Figueroa, Carolina; Kronberg, Udo; Simian, Daniela; Pizarro, Gonzalo; Castro, Magdalena; Piottante, Antonio; Vial Maria, Teresa; Quera, Rodrigo
Abstract : Background: Mucosal healing has become a therapeutic goal in Ulcerative Colitis (UC) since this has been shown to reduce the likelihood of clinical relapse, risk of surgery, and hospitalisation. However, histological remission has been proposed as an additional predictive marker in the progression of the disease and therapeutic response. Several studies have demonstrated that histological remission is associated with reduction in hospitalizations and surgery. The aim of this study was to determine the correlation between clinical, endoscopical and histological activity. Methods: A correlational analytic cross-sectional study was performed including adult patients with UC who underwent colonoscopy between February and July 2016 in our center. Clinical activity was determined with Partial Mayo Subscore (PMS). Endoscopical activity was assessed with Mayo Endoscopic Subscore (MES) and Mayo Modified Endoscopic Score (MMES). Biological activity was determined with Fecal Calprotectin (FC). Finally, histological activity was assesed with Geboes Score (GS) and the presence of basal plasmocytosis (BP). Scores were analyzed with Spearman's rank correlation coefficient test (rho). Patients with concomitant Clostridium difficile or cytomegalovirus infection were excluded. Results: 53 patients with a total of 59 endoscopic procedures were included (60% female, median age 33 yr [r: 18–69], median disease duration 4 yr [r: 0–39]). Extension of the disease at diagnosis was 19% proctitis, 41.5% left sided colitis and 39.5% pancolitis. Extraintestinal manifestations were reported in 51% of the patients. Mesalamine, immunomodulators and anti-TNF therapy was used in 76%, 27%, and 7% of the cases respectively. In 61% of the procedures the mucosa was inflamed (MES 2–3) while histological activity (GS > 3.1) was present in all, except for one patient. Endoscopic remission (MES 0–1) was observed in the other 39% of procedures; however, 40% of these exhibited histological inflammation in their biopsies. The PMS had a regular correlation with MES and MMES (rho = 0.53/ P = 0.001 and rho = 0.50/ P = 0.001 respectively), and with GS and BP correlated badly (rho = 0.42/ P = 0.008 and rho = 0.32/ P = 0.01 respectively). There was a good correlation between MES and MMES (rho = 0.81/ P = 0.001), while with GS and PB was regular (rho = 0.72/ P = 0.001 and rho = 0.62/ P = 0.001 respectively). Even though MES correlated regularly with GS, there was a positive correlation between these 2 parameters, as at higher GS, a higher MES. MMES correlated regularly with GS and BP (rho = 0.67/ P = 0.001 and rho = 0.57/ P = 0.001). FC had bad correlation with PMS (rho = 0.35/ P = 0.057), while with MES, MMES, GS and BP was regular (rho = 0.79/ P = 0.001, rho = 0.79/ P = 0.001, rho = 0.64/ P = 0.001 and rho = 0.53/ P = 0.002 respectively). Conclusions: Our study confirms that PMS is not a reliable indicator of inflammatory activity. On the other hand, histological activity had a regular correlation with endoscopic activity, which suggests that endoscopic remission might not be enough. Prospective studies will allow defining the usefulness of histologic remission as ultimate goal.